SOEP-Core - 2020: Sampling, nonresponse, and weighting in the IAB-SOEP migration studies M7 and M8 - Hans Walter Steinhauer; Parvati Trübswetter; Sabine Zinn (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper provides details on sampling design, fieldwork, nonresponse and population adjustments for the 2020 samples M7 and M8 of the Socio-Economic Panel (SOEP). Sample M7 refreshes the SOEP core sample, especially samples M1 and M2, including households with household heads having a Bulgarian, Polish, or Romanian nationality. The sample M8 augments the SOEP core sample, sampling households of foreigners from third countries to evaluate the "Fachkräfteeinwanderungsgesetz." Obtaining nearly 1,000 household interviews and panel consent of households for each sample was complicated by the first wave of the Corona pandemic and the first lockdown. Nevertheless, nonresponse on the household level is driven by a variety of characteristics, such as nationality or regional contexts as well as information contained in the Integrated Employment Biographies.
Keywords: 330